The late stage of Parkinson's –results of a large multinational study on motor and non-motor complications. (June 2020) - Schrag, A.; Hommel, A.L.A.J.; Lorenzl, S.; Meissner, W.G.; Odin, P.; Coelho, M.; Bloem, B.R.; Dodel, R.; ,; Ferreira, Joaquim; Fabbri, Margherita; Tison, François; et al.
Abstract: Introduction: There is little information on the late stages of parkinsonism. Methods: We conducted a multicentre study in 692 patients with late stage parkinsonism in six European countries. Inclusion criteria were disease duration of ≥7 years and either Hoehn and Yahr stage ≥4 or Schwab and England score of 50 or less. Results: Average disease duration was 15.4 (SD 7.7) years and mean total UPDRS score was 82.7 (SD 22.4). Dementia according to MDS-criteria was present in 37% of patients. Mean levodopa equivalence dose was 874.1 (SD 591.1) mg/d. Eighty two percent of patients reported falls, related to freezing (16%) or unrelated to freezing (21% of patients) or occurring both related and unrelated to freezing (45%), and were frequent in 26%. Moderate-severe difficulties were reported for turning in bed by 51%, speech by 43%, swallowing by 16% and tremor by 11%. Off-periods occurred in 68% and were present at least 50% of the day in 13%, with morning dystonia occurring in 35%. Dyskinesias were reported by 45% but were moderate or severe only in 7%. Moderate-severe fatigue, constipation, urinary symptoms and nocturia, concentration and memory problems were encountered by more than half of participants. Hallucinations (44%) or delusions (25%) were present in 63% and were moderate-severe in 15%. The association with overall disability was strongest for severity of falls/postural instability, bradykinesia, cognitive score and speech impairment. Conclusion: These data suggest that current treatment of late stage parkinsonism in the community remains insufficiently effective to alleviate disabling symptoms in many patients. Highlights: The most common complications were falls, off-periods, speech and swallowing problems, and autonomic and psychiatric complications, fatigue and dementia. Despite moderate doses of levodopa only 7% had moderate to severe dyskinesia. Disability was predominantly influenced by motor severity, overall bradykinesia and axial features but also speech impairment.